The Correlation Between Principal’s Gender, School Geography and School Success - Camara, Jun S. (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Gender equality as a sustainable development goal is hoped to neutralize the influence of gender differences in all development sectors, including education. This region-wide survey among elementary school administrators (n=1626) in the Philippines revealed that the ratio of female-to-male administrators is 2:1. Profiling of the target respondents showed that more women finished their doctoral degrees and that the majority of the administrators are non-holders of a principal position for both genders and that both genders only have their highest level of relevant training and professional affiliation at the 'division level,' with very limited participation to international level. Further, statistical analysis showed that gender and school geography have a highly significant correlation, though the strength of the association is weak. Furthermore, gender correlates with age, civil status, highest educational attainment, and none with others, while geography correlates with the highest professional training and affiliation. The computed means of the school success indicators are high. However, none correlate with either gender and geography, except for average monthly MOOE utilization, which shows a highly significant correlation with geography, implying that schools in rural areas have lower utilization than those in urban areas. Interestingly, though the association is 'weak,' analysis shows that male administrators are associated with higher promotion rates, completion rates, mean percentage scores, and average monthly MOOE utilization. Policy recommendations are provided to address the issues found.